Family Affective Function: A Phenomena Adolescents In Boarding School - Mutmainnah, Sofia; Waliyanti, Ema (Proceeding Universitas Muhammadiyah Yogyakarta Graduate Conference, 2020)
Background: Affective function of family is an important role in the lived of boarding school adolescents. Family affective functions that are not fulfilled by parents had an adolescents impact such as withdrawing from relationships, distraction from concentration, delinquency and even depression because adolescents feel unnoticed and loved. The responsibility of parents towards adolescents is guide, educate and provide the needs of adolescents, including emotional so that affective family functions can be fulfilled. Methods:This research uses qualitative method of phenomenology approach. The data were collected through focus group discussion and in-depth interviews. Participants in the study numbered 29 people consisting of adolescents, parents and teachers of boarding school determined with purposive sampling. Data validity uses triangulation of sources, methods, peer debriefing, and thick description. Data analysis using open code 4.03. Results: The results showed several factors that affect the family affective function in adolescents in boarding schools are motivation to enter the boarding school, boarding school policies, communication with boarding schools and barriers to adolescents communication with parents. Fulfillment of affective functions that parents can fulfill as adolescents at boarding schools are the attachment of parents with adolescents, communication of parents with adolescents, guidance of parents, giving adolescent needs and giving rewards to adolescents. Conclusion: Fulfillment of family affective functions in adolescents at boarding school is an important thing that must be given by parents because as one of the responsibilities that must be fulfilled for adolescents. Parents are expected to give affection and attention to adolescents so that adolescents feel valued, loved and achieved emotional comfort in adolescents.